PEMETAAN POLA TABUHAN BONANG PENERUS: SEBUAH UPAYA PELESTARIAN KARAWITAN GAYA YOGYAKARTA - Tri Suhatmini Rokhayatun; Setya Rahdiyatmi Kurnia Jatilinuar (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2022)
Bonang is one of the essential instruments in the Yogyakarta-style musical, especially in strengthening the Yogyakarta-style musical wasp pattern. There are no notes or special learning modules for the bonang Yogyakarta style, so that indirectly there is a problem in the bonang transmission process in the education process. First, it complicates the teaching and learning process. Second, the learning process becomes ineffective. Third, minimal reading materials impact the lack of literature for students, which results in the method of transmitting working patterns not running optimally. Therefore, to compile a definite way of Yogyakarta-style bonang, it is necessary to make an effort to map various models of Yogyakarta-style garap bonang interpretations as writing or treatise, which later becomes material in lectures on the practice of karawitan style. Yogyakarta. The specific purpose of this study was to record and document the work of the Yogyakarta-style wasp bonang. The method used in this study is a qualitative method with data collection techniques of observation, literature study, questionnaires, and interviews. While the data analysis techniques used are data reduction, data presentation, data verification. The results of this study are in the form of reports, journals, and Yogyakarta-style bonang learning modules.